Double-Hit Gene Expression Signature Defines a Distinct Subgroup of Germinal Center B-Cell-Like Diffuse Large B-Cell Lymphoma - Ennishi, Daisuke; Jiang, Aixiang; Boyle, Merrill; Collinge, Brett; Grande, Bruno M; Ben-Neriah, Susana; Rushton, Christopher; Tang, Jeffrey; Thomas, Nicole; Slack, Graham W; Farinha, Pedro; Takata, Katsuyoshi; et al. (Journal of clinical oncology, 2019)
High-grade B-cell lymphoma with MYC and BCL2 and/or BCL6 rearrangements (HGBL-DH/TH) has a poor outcome after standard chemoimmunotherapy. We sought to understand the biologic underpinnings of HGBL-DH/TH with BCL2 rearrangements (HGBL-DH/TH- BCL2) and diffuse large B-cell lymphoma (DLBCL) morphology through examination of gene expression. We analyzed RNA sequencing data from 157 de novo germinal center B-cell-like (GCB)-DLBCLs, including 25 with HGBL-DH/TH- BCL2, to define a gene expression signature that distinguishes HGBL-DH/TH- BCL2 from other GCB-DLBCLs. To assess the genetic, molecular, and phenotypic features associated with this signature, we analyzed targeted resequencing, whole-exome sequencing, RNA sequencing, and immunohistochemistry data. We developed a 104-gene double-hit signature (DHITsig) that assigned 27% of GCB-DLBCLs to the DHITsig-positive group, with only one half harboring MYC and BCL2 rearrangements (HGBL-DH/TH- BCL2). DHITsig-positive patients had inferior outcomes after rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone immunochemotherapy compared with DHITsig-negative patients (5-year time to progression rate, 57% and 81%, respectively; P < .001), irrespective of HGBL-DH/TH- BCL2 status. The prognostic value of DHITsig was confirmed in an independent validation cohort. DHITsig-positive tumors are biologically characterized by a putative non-light zone germinal center cell of origin and a distinct mutational landscape that comprises genes associated with chromatin modification. A new NanoString assay (DLBCL90) recapitulated the prognostic significance and RNA sequencing assignments. Validating the association with HGBL-DH/TH- BCL2, 11 of 25 DHITsig-positive-transformed follicular lymphomas were classified as HGBL-DH/TH- BCL2 compared with zero of 50 in the DHITsig-negative group. Furthermore, the DHITsig was shared with the majority of B-cell lymphomas with high-grade morphology tested. We have defined a clinically and biologically distinct subgroup of tumors within GCB-DLBCL characterized by a gene expression signature of HGBL-DH/TH- BCL2. This knowledge has been translated into an assay applicable to routinely available biopsy samples, which enables exploration of its utility to guide patient management.